A STUDY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF STATE POLYTECHNIC OF BENGKALIS IN COMPLETING SENTENCES WITH CORRECT GERUND AND TO INFINITIVE VERB FORM - Aswandi Aswandi; A Malik; Boni Saputra (INOVISH JOURNAL, 2018)
Mastering grammar is important in learning English. In grammar, the words pattern and tenses should be considered as main focus for the discussion. Therefore, this study aimed to find out the ability of the students in completing sentences with correct gerund and to infinitive verb forms . This research wasÂ  a descriptive research. This study showed that the level of the students ability was at mediocre level. It was at 53. The error commonly occured slighly the same in completing both gerund and to infinitive verb forms. The average score of gerund was 52 and 54 points for to infinitive.